Cognitive Operations Models that Open the Black Box and Predict our Decisions - Katsikopoulos, Konstantinos V. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"Attempts to improve decision-making are unlikely to succeed without an understanding of how and why people currently make choices. In this accessible and fascinating book, Konstantinos Katsikopoulos shows how mathematical models of decision processes in operational settings can provide this understanding. Alternative modelling approaches are contrasted, and clear criteria provided to determine whether a model is likely to provide useful insights in a range of practical situations. Managers facing decisions in a risky and uncertain world and researchers in the field of operations will have much to gain from the ideas presented here". -Paul Goodwin, Emeritus Professor, University of Bath, UK "Professor Katsikopoulos challenges established theories and beliefs. If you care about diversity of thought, this book is a must-read. It will provide you with new perspectives and research ideas". -Enno Siemsen, Patrick A. Thiele Distinguished Chair in Business, Wisconsin School of Business, USA This book examines how people make decisions under risk and uncertainty in operational settings and opens the black box by specifying the cognitive processes that lead to human behavior. Drawing on economics, psychology and artificial intelligence, the book provides an innovative perspective on behavioral operations. It shows how to build optimization and heuristic decision-making models, compares the models on various dimensions such as predictive power and transparency, and discusses interventions for improving human behavior. This book will be particularly valuable to academics and practitioners who seek to select a modeling approach that suits the operational decision at hand. Konstantinos V. Katsikopoulos is Professor of Behavioral Science at the University of Southampton, where he is the research director of the Business School. Previously, he was a visiting Assistant Professor at the Massachusetts Institute of Technology, Senior Research Scientist at the Max Planck Institute for Human Development and a German Science Foundation Fellow. Konstantinos is an internationally leading researcher in the interdisciplinary study of decision making, helping shape the field of behavioral operations research and chairing the behavioral group at the OR Society.
Introduction: Why cognitive operations? -- Chapter 1: Approaches to cognitive modelling -- Chapter 2: Decisions under risk -- Chapter 3: Strategic interactions -- Chapter 4: Newsvendor problems -- Chapter 5: Decisions under uncertainty -- Chapter 6: Conclusions: The future of cognitive modelling is ahead.
Keywords: Production management; Operations research; Operations Management; Operations Research and Decision Theory